Evaluation of the frequency, follow-up, and treatment of patients with multisystem inflammatory syndrome related to COVID-19 - Oncul, Mehmet; Karakurt, Cemsit; Elkiran, Ozlem; Tekin, Mehmet; Gozukara Bag, Harika Gozde (Annals of Medical Research, 2022)
Aim: Aim of this study is evaluate the clinical features, laboratory values, treatment and follow-up of in children with COVID-19-associated multisystem inflammatory syndrome (MIS-C) disease.Materials and Methods: In this study, patients aged between 2 months and 17 years, who applied to the Inonu University Faculty of Medicine, Department of Pediatrics between March 2020, and February 2021 due to MIS-C related to COVID-19 disease, were reviewed retrospectively. Demographic data, clinical features, laboratory values, treatment and follow-up data of the patients were evaluated.Results:  Forty-nine patients diagnosed with MIS-C between March 2020 and February 2021 were included in the study. Thirty-one (72.7%) patients were male and 18 (27.3%) were female. The most common indications for admission were fever (100%), abdominal pain (51.6%), vomiting (42.9%), cough (38.8%), diarrhea (28.8%), shortness of breath, rash, conjunctivitis, and convulsion. Levels of CRP (93.9%), D-dimer (85.7%), fibrinogen (73.4%), interleukin 6 (IL6) (73.4%), procalcitonin (71.4%), NT-proBNP (63.2%) remained at high levels in respective number of patients. The (32.6%) patients were followed up in the intensive care unit. These patients had cardiogenic shock (26.5%), severe pneumonia (18.3%), and acute gastroenteritis (14.3%). It was determined that the mean age of the patients followed up for cardiogenic shock was 12.5 years and relatively higher (p
Keywords: Multi-system inflammatory syndrome; COVID 19; SARS Cov-2